The IISS armed conflict survey 2015 the worldwide review of political and humanitarian trends in current conflicts (Routledge for the International Institute for Strategic Studies, 2015)
Annual publication that provides yearly data on fatalities, refugees and internally displaced people for all major armed conflicts, alongside in-depth analysis of their political, military and humanitarian dimensions. The first edition of the book covers the key developments and context of more than 40 conflicts, including those in Afghanistan, Democratic Republic of Congo, Iraq, Myanmar, Syria and Yemen.